Characterization of Bacterial Etiologic Agents of Biofilm Formation in Medical Devices in Critical Care Setup - Sangita Revdiwala; Bhaumesh M. Rajdev; Summaiya Mulla (Critical Care Research and Practice)
Background. Biofilms contaminate catheters, ventilators, and medical implants; they act as a source of disease for humans, animals, and plants. Aim. Critical care units of any healthcare institute follow various interventional strategies with use of medical devices for the management of critical cases. Bacteria contaminate medical devices and form biofilms. Material and Methods. The study was carried out on 100 positive bacteriological cultures of medical devices which were inserted in hospitalized patients. The bacterial isolates were processed as per microtitre plate. All the isolates were subjected to antibiotic susceptibility testing by VITEK 2 compact automated systems. Results. Out of the total 100 bacterial isolates tested, 88 of them were biofilm formers. A 16–20-hour incubation period was found to be optimum for biofilm development. 85% isolates were multidrug resistants and different mechanisms of bacterial drug resistance like ESBL, carbapenemase, and MRSA were found among isolates. Conclusion. Availability of nutrition in the form of glucose enhances the biofilm formation by bacteria. Time and availability of glucose are important factors for assessment of biofilm progress. It is an alarm for those who are associated with invasive procedures and indwelling medical devices especially in patients with low immunity.